(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: The seeds of Monodora myristica, a tropical plant belonging to the family Annonaceae, are widely used as condiments in the preparation of a number of African delicacies, to impart or enhance flavour. Their use is largely due to the volatile and fixed oils contained in the nuts. Objective: To screen for the acute toxicity (LD50) profile, determine the physicochemical properties, as well as carry out GC-MS analysis of the seed oil of Monodora myristica. Method: The acute toxicity screening was done using Lorke’s method. Physicochemical profile of the oil was determined using standard methods. GC-MS analysis of the oil sample was also carried out, using Shimadzu GCMS-QP2010SE. Results: The acute toxicity study showed that the oil sample had an LD50 of 316 mg/kg. The acid value was determined to be 9.27 mg KOH/g oil, while saponification value was 194.95 mg KOH/g oil. GC-MS analysis of the oil revealed that it contained fatty acids such as n-hexadecanoic acid, cis-vaccenic acid and 9,12-octadecadienoic acid; as well as terpinoids such as alpha-terpineol and alpha-cadinol. Conclusion: Results of the toxicological screening indicates that Monodora myristica oil is moderately toxic as the LD50 was within 50 – 500 mg/kg range. The oil has a relatively high tendency to go rancid due to the high acid value of 9.27 mg KOH/g oil.